Etika Kerja Pegawai Pada Kantor Camat Denpasar Barat Kota Denpasar - Yunita, I Made; I. G. N. A. Sedana Harta; I G. P. Yasa; I. K. T. E. Putra (Universitas Tabanan, 2026)
Amidst the digital transformation and efforts to restore an inclusive economy in Bali, the work ethic of government officials is a crucial foundation for public service. This study evaluates the work ethic of employees at the West Denpasar District Office, the spearhead of the bureaucracy, directly in touch with the dynamics of urban society. This analysis aims to map the quality of work ethic based on the theoretical perspectives of Utilitarianism and Deontology, and its relationship to professionalism in the digital economy era. This study used a descriptive quantitative approach with a total sampling technique of 45 respondents. Data were collected through a questionnaire covering 12 work ethic indicators and analyzed using frequency distribution and interval analysis techniques. The findings indicate that the overall work ethic of employees is in the